FREQUENCY OF CLINICAL PHENOTYPES OF JUVENILE MYOCLONIC EPILEPSY: PILOT STUDY IN SIBERIAN FEDERAL DISTRICT - N. A. Shnayder; O. S. Shilkina; K. V. Petrov; A. V. Duyzhakova; N. A. Marueva (Эпилепсия и пароксизмальные состояния, 2016)
Objective.   The analysis of the frequency of occurrence of clinical phenotypes of JME among residents  of the Siberian Federal District (Russia). Materials  and  Methods.  80 patients with JME underwent preliminary anamnestic  and clinical selection  using  stratified randomization.  After verification of  their diagnosis,  patients  were  grouped  based  on  the phenotype  classification proposed  by Martínez-Juárez  et al (2006).  Gender was also noted  for subsequent  genderrelated analysis. Results.   The incidence of JME among males was lower than among females.  In general, the average JME onset age was characteristic for this clinical form of idiopathic generalized epilepsy. Furthermore, JME onset age in males  was higher than in females.  In general, the most  frequent phenotype  was the classical Type I phenotype.  The frequency  of Type I  occurrence  in males  was  significantly higher than that in females.  Type II,  the  least  favorable phenotype  in terms  of stable pharmacological remission,  occurred 3.5 times  less  frequently  in  males  compared  to females.  Types III and IV did not reveal significant gender-related differences.  Conclusions. The results allow to revise the initial diagnosis of JME in burdened families: we recommend video-EEG monitoring in adolescent female patients at a younger age, with mandatory testing of levels of consciousness during induced stress. Higher frequency of Type II JME in females  suggests imminent  need for dynamic and lengthy video-EEG monitoring to exclude the chance of pseudo remission, before a decision can be made about reduction or termination of AEDs.